Placing blame or a call to action? An analysis of Uwezo in the Kenyan press - Jeremy Monk (Arizona State University, 2020)
Citizen-led assessments were developed in the mid-2000s to gather evidence on children's learning outcomes following the rapid increase in primary student enrolment in the developing world. Integral to their philosophy is social accountability and community engagement. While most large-scale assessments focus on test-based accountability to promote policy shifts, citizen-led assessments, utilizing the information-accountability causal chain, theorize that information of low learning outcomes, disseminated widely, will engage stakeholders in activities and debates, ultimately leading to improvements in education quality and service delivery. This paper examines Uwezo, the oldest citizen-led assessment in East Africa, and its portrayal in the Kenyan print media. I explore whether discourse concerning Uwezo exposes education quality issues while promoting citizen engagement and how Uwezo's social accountability philosophy is used in public discourse through the lens of political evolutionary mechanisms. I find that Uwezo's findings were prominently discussed beginning in 2013, but that shock value of low learning levels has since decreased. Moreover, public discourse has highlighted cross-national and provincial/county comparisons in achievement levels while focusing on blaming teachers and the education system's culture. Although Uwezo has succeeded in disseminating its findings widely in Kenya, there is minimal engagement in public discourse with its social accountability and community engagement philosophy and discourse does not promote citizen action on a national level. As Uwezo has become a respected education policy player in East Africa, and globally, it must find ways to engage communities to act upon its findings to directly improve education quality.